Nitrogen Limitation of the Summer Phytoplankton and Heterotrophic Prokaryote Communities in the Chukchi Sea - Mills, Matthew M.; Brown, Zachary W.; Laney, Samuel R.; Ortega-Retuerta, Eva; Lowry, Kate E.; van Dijken, Gert L.; Arrigo, Kevin R. (Frontiers in Marine Science, 2018)
Major changes to Arctic marine ecosystems have resulted in longer growing seasons with increased phytoplankton production over larger areas. In the Chukchi Sea, the high productivity fuels intense benthic denitrification creating a nitrogen (N) deficit that is transported through the Arctic to the Atlantic Ocean, where it likely fuels nitrogen fixation. Given the rapid pace of environmental change and the potentially globally significant N deficit, we conducted experiments aimed at understanding phytoplankton and microbial N utilization in the Chukchi Sea. Ship-board experiments tested the effect of NO3- additions on both phytoplankton and heterotrophic prokaryote abundance, community composition, photophysiology, carbon fixation and NO3- uptake rates. Results support the critical role of NO3- in limiting summer phytoplankton communities to small cells with low production rates. NO3- additions increased particulate concentrations, abundance of large diatoms, and rates of carbon fixation and NO3- uptake by cells >1 µm. Increases in the quantum yield and electron turnover rate of photosystem II in NO3- treatments suggested that phytoplankton in the ambient dissolved N environment were N starved and unable to build new, or repair damaged, reaction centers. While some increases in heterotrophic prokaryote abundance and production were noted with NO3- amendments, phytoplankton competition or grazers likely dampened these responses. Trends toward a warmer more stratified Chukchi Sea will likely enhance summer oligotrophic conditions and further N starve Chukchi Sea phytoplankton communities.